Intramolecular Olefin Diamination for the Stereoselective Synthesis of 3-Aminopiperidines - Kong, Aidi; Blakey, Simon B. (Synthesis, 2012)
A general method for the direct intramolecular diamination of terminal olefins is presented. The reaction, mediated by hypervalent iodine oxidants, produces substituted 3-aminopiperidine scaffolds with high regio- and stereoselectivity, rendering this process relevant to both medicinal chemistry and natural products synthesis.
Keywords: diamination; hypervalent iodine; oxidation; catalysis; piperidine